2017
DOI: 10.1111/clr.13008
|View full text |Cite
|
Sign up to set email alerts
|

Costs and clinical outcomes of implant placement during ablative surgery and postponed implant placement in curative oral oncology: a five‐year retrospective cohort study

Abstract: Placing implants during ablative surgery lowered the individual costs of implant placement and led to more patients with functioning dentures, while implant failure and loading were comparable to postponed placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 47 publications
(102 reference statements)
0
33
0
Order By: Relevance
“…Despite this fact, Mizbah et al and Schepers et al both agree that nonfunctional primary placed implants remain less expensive than a secondary surgery. Wetzels et al found similar results, although their opinion needs to be supported by more scientific results.…”
Section: Discussionmentioning
confidence: 84%
“…Despite this fact, Mizbah et al and Schepers et al both agree that nonfunctional primary placed implants remain less expensive than a secondary surgery. Wetzels et al found similar results, although their opinion needs to be supported by more scientific results.…”
Section: Discussionmentioning
confidence: 84%
“…Intra-and postoperative complications of dental implant placement were uncommon. The most common reported complication was osteoradionecrosis (ORN) in irradiated patients (Ch'ng et al, 2015;Korfage et al, 2014;Wetzels et al, 2016Wetzels et al, , 2017. The ORN rate varied between 1.8% and 7.7%.…”
Section: Complicationsmentioning
confidence: 99%
“…In the Netherlands, the costs of implant rehabilitation in head and neck cancer patients are covered by the insurance which makes primary immediate implant placement an actual treatment option. A study of Wetzels et al [39] on costeffectiveness stated that individual costs of implant placement during ablative surgery have shown to be lower when compared to postponed placement, but that factors as oncological prognosis and overall life expectancy must be taken into account when considering placing implants during ablative surgery. The same conditions should apply for immediate implant placement.…”
Section: Discussionmentioning
confidence: 99%